2021
DOI: 10.1155/2021/3056428
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Analysis of Sports Injury Estimation Model Based on Mutation Fuzzy Neural Network

Abstract: In recent years, with the gradual development of sports, the competition between athletes is becoming more and more fierce. The long training time and heavy body load of athletes lead to the increase of the incidence of sports injury, and the evaluation and analysis of athletes’ sports injury need a lot of manpower and material resources. In order to improve the calculation efficiency of sports injury estimation results and save the cost of estimation and analysis, we propose a sports injury estimation model b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…In the field of national fitness, research focuses are mainly on fitness feedback, nutritious diet, and intelligent equipment. Wang and Yang [ 12 ] carried out research on the assessment of sports injury based on neural network. Novatchkov and other scholars [ 13 ] analyzed the training plan and training feedback of artificial intelligence strength training in the fitness process.…”
Section: Intelligent Sports: Rise Development and Applicationmentioning
confidence: 99%
“…In the field of national fitness, research focuses are mainly on fitness feedback, nutritious diet, and intelligent equipment. Wang and Yang [ 12 ] carried out research on the assessment of sports injury based on neural network. Novatchkov and other scholars [ 13 ] analyzed the training plan and training feedback of artificial intelligence strength training in the fitness process.…”
Section: Intelligent Sports: Rise Development and Applicationmentioning
confidence: 99%
“…They found that the fuzzy neural network outperformed Bayesian and Lagrange models. However, this was a theoretical proposal using simulated data [ 51 ]. Another 2021 paper by Zhang et al proposed a grey neural network that inputs the results of n-grey models into a neural network for final prediction.…”
Section: Reviewmentioning
confidence: 99%
“…They discovered that the fuzzy neural network performed much better than the Bayesian and Lagrange models. Having that, this was just a theoretical proposition that used simulated data [81]. In another research published in 2021, Zhang et al suggested a grey neural network.…”
Section: Fuzzy and Neural Networkmentioning
confidence: 99%